Technology-Intensive Suppliers as a Key Element for Structural Change in Latin America - Torres-Zapata, I (IGI Global, 2014)
The current increase of commodity prices prompts the question regarding the extent to which the growth of primary industries is used as a basis of industrial development. Empirical evidence suggests the development of Technology-Intensive Suppliers (TIS) has played an important role in the industrialization process of the Nordic countries, Canada, and Australia. The development of local TIS may contribute to both reinforcing the industrial base and supporting structural change in developing countries. Therefore, it may provide a way to advance from natural resource dependence towards knowledge-based industrial activities. The TIS products are created under tailor-made concepts, giving solutions to their customers. TIS use knowledge and customer information to create innovation. These firms enhance value chains improving customer s competitive advantages (Dornberger & Torres, 2006). The relationship between the primary sector and its suppliers of technology can be seen as a backward linkage. Sectors with linkages of this kind use inputs from other industries (Hirschman, 1958). Hence, a fundamental goal of research in the context of developing countries is to understand the development of TIS and analysis of their improvement as a result of entrepreneurship intervention. This chapter covers the relevance of TIS firms in developing countries. TIS companies are frequently labeled as Micro-, Small-, and Medium- Sized Enterprises (MSMEs). In conclusion, the findings highlight the need to pay more attention to TIS organizations in developing economies. In Latin America, TIS firms contribute to the employment and diversification of the economic structure of the region through value-added products and services. © 2014 by IGI Global. All rights reserved.